Analisis Faktor-Faktor yang Mempengaruhi Keputusan Petani Menjual Tembakau dengan Sistem Tebasan yang Ditinjau dalam Persepektif Ekonomi Islam - Saputra, Solehan; Hikmatul Lutfi’ah; Nurul Lailatul Vitriyah (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
This study aims to analyze various factors influencing the decisions of tobacco farmers in Wuluhan District, Jember Regency, in using the tebasan (bulk sale before harvest), and how this is viewed from the perspective of Islamic economics. The variables examined include income, farming experience, education level, and the perspective of Islamic economics, whose influence on selling decisions was tested using a quantitative approach through Structural Equation Modeling (SEM) with the help of SmartPLS software. The results of the study show that: Income, farming experience, and education do not have a direct significant effect on the decision to sell tobacco .However, these three variables have an indirect effect through the variable of the Islamic economic perspective.The Islamic economic perspective is proven to play a significant role as a mediating variable, influencing farmers' decisions to sell tobacco. In practice, the tebasan system does offer efficiency and certainty for farmers, but it contains elements of uncertainty (gharar) that must be critically reviewed in the context of Islamic sales law.